THE IMPACTS OF TEACHER SUPPORTIVE MOTIVATIONAL DISCOURSE INTERVENTION ON LANGUAGE ACHIEVEMENT: MASTERY- VS PERFORMANCE-AVOIDANT EAP LEARNERS - Elham Sadat Mirian; Esmaeel Ali Salimi (TEFLIN Journal, 2025)
This interventional study examines whether the language achievement of mastery-avoidant and performance-avoidant English for Academic Purposes (henceforth EAP) students can be improved through the teacher supportive motivational discourse (TSMD). This study also explores how the students perceive the effects of this discourse on their language achievement. To this end, we purposively selected 99 EAP students, of whom we placed 31 students in a control group, and the rest, mastery-avoidant (henceforth MAV) and performance-avoidant (henceforth PAV) participants, into two equal intervention groups. Then, we assessed both groups’ L2 achievement using an achievement test (the end-of-semester test prepared based on the EAP book) before and after a ten-week intervention. To understand the perceptions of the students about the intervention, we conducted semi-structured interviews with 20 students who were purposively selected based on their willingness to participate. Out of the 20 students, 10 were purposively chosen to reflect on key episodes related to TSMD and explain the reason behind their actions. Statistical analysis (non-parametric ANCOVA) carried out in the quantitative phase revealed that in comparison to the control group, the intervention group’s achievement was significantly higher. However, the differences between both intervention groups were slight. Content analysis in the qualitative phase also showed that the intervention effect on students’ achievement was mediated by learners’ autonomy and willingness to communicate (henceforth WTC). The implications of this intervention for enhancing teachers’ performance and students’ learning are discussed.